Metformin improves age-related visual cortex dysfunction in mice by reducing noise correlation in the primary visual cortex - Liu, Xiaoming; Zhou, Yifeng; Liu, Jiachen; Xu, Guangwei (Frontiers in Aging Neuroscience, 2025)
IntroductionAge-related decline in visual processing has been observed in association with reduced orientation selectivity and decreased signal-to-noise ratios in the primary visual cortex (V1). Elevated noise correlations between neurons are associated with impaired visual discrimination in aging; however, less is known about therapeutic interventions that could preserve visual cortical function during aging. In this study, we investigated the effects of metformin treatment on age-related changes in visual processing and neuronal correlations in V1.MethodsWe conducted in vivo electrophysiological recordings to investigate whether 3 weeks of acute gavage with metformin improves visual processing in 12-month-old mice compared to 8-week-old mice by modulating neural noise in the V1, and used western blot analysis to investigate the molecular mechanism of the effect of metformin.ResultsIn vivo electrophysiological recordings revealed that aging led to V1 neuronal hyperactivity, accompanied by reduced orientation selectivity, a decreased signal-to-noise ratio, and increased response variability. Notably, aged mice exhibited increased noise correlation, response covariance, and population variability. Analysis of fast-spiking interneurons revealed impaired noise suppression in the inhibitory circuits of aged mice. Daily metformin treatment reversed these age-related alterations by improving fast-spiking neuron-mediated decorrelation and reducing noise correlation. Mechanistically, metformin upregulated the protein expression levels of glutamic acid decarboxylase 67 and gephyrin, key components of inhibitory synapses, suggesting that metformin enhances visual processing by strengthening inhibitory signaling and reducing the correlated variability in the V1.DiscussionMetformin treatment effectively ameliorated these deficits through enhanced GABAergic signaling; however, the broader therapeutic mechanisms across sensory systems remain unclear. In this study, we demonstrate that metformin preserves visual function by restoring excitatory-inhibitory balance, suggesting a promising approach for age-related sensory decline.